Monitoring transmissibility and mortality of COVID-19 in Europe - Yuan, Jing; Li, Minghui; Lv, Gang; Lu, Z. Kevin (International journal of infectious diseases, 2020)
•As of March 10, 2020, Italy had reported 9172 COVID-19 cases with 463 deaths.•We report the real-time reproductive numbers (R(t)) and case fatality rates for selected European countries (Italy, France, Germany, and Spain) by March 9, 2020.•The R(t) was greater than 2 in the selected European countries, indicating that the outbreak will continue. As a global pandemic is inevitable, real-time monitoring of transmission is vital for containing the spread of COVID-19. The main objective of this study was to report the real-time effective reproduction numbers (R(t)) and case fatality rates (CFR) in Europe. Data for this study were obtained mainly from the World Health Organization website, up to March 9, 2020. R(t) were estimated by exponential growth rate (EG) and time-dependent (TD) methods. ‘R0’ package in R was employed to estimate R(t) by fitting the existing epidemic curve. Both the naïve CFR (nCFR) and adjusted CFR (aCFR) were estimated. With the EG method, R(t) was 3.27 (95% confidence interval (CI) 3.17–3.38) for Italy, 6.32 (95% CI 5.72–6.99) for France, 6.07 (95% CI 5.51–6.69) for Germany, and 5.08 (95% CI 4.51–5.74) for Spain. With the TD method, the R value for March 9 was 3.10 (95% CI 2.21–4.11) for Italy, 6.56 (95% CI 2.04–12.26) for France, 4.43 (95% CI 1.83–7.92) for Germany, and 3.95 (95% CI 0–10.19) for Spain. This study provides important findings on the early outbreak of COVID-19 in Europe. Due to the recent rapid increase in new cases of COVID-19, real-time monitoring of the transmissibility and mortality in Spain and France is a priority.